Effect of Cooking and Solar Drying on the ‘In vitro’ and ‘In vivo’ Digestibility of Okra According to the Different Stages of Maturity - , N’guessan Yao Firmin; , Konan Brou Roger; , Assemand Emma Fernande (Archives of Current Research International, 2018)
Aims: The study aimed to assess the nutritional profile and the ‘in vitro’ and ‘in vivo’ digestibility of two varieties of okra (Abelmoschus caillei and Abelmoschus esculentus), sun-dried and water-cooked, to determine the best harvest stage showing the best nutritional and digestibility profiles. Place and Duration of Study: University of Felix Houphouet Boigny, Abidjan, Côte d’Ivoire, between January and February, 2018. Methodology: Plant material was harvested at four different stages of maturity (at 5, 10, 15 and 20 days after flowering) on an experimental field. Some macroscopic parameters, ‘in vitro’ and ‘in vivo’ digestibility of the both okra’s varieties were determined. Results: There was a significant increase in digestibility (in vitro) until the 15th day of provide maturity before falling at the 20th day for both varieties. The two treatments thus find their best nutritional and digestibility levels at 15 days after maturity. The highest fresh okra digestibility rates are 0. 120 mg / 100 g DM and 0.70 mg / 100 g DM respectively for the Koto’s and Tomi’s variety at 15 days of maturity. In terms, the ‘in vivo’ digestibility results indicate that okra promotes the digestion of food and minerals. This digestibility of food is better with Tomi’s variety (1.35 mg / 100 g) in the dried form than Koto (0.44 mg / 100 g). Conclusion: Okra dried under the sun with its high fibre level, could be considered as a dietetic food intended to prevent or to treat constipation, obesity, hyperlipemia, diabetes, some chronic diarrhoea and cancer. Also, cooking and drying processes could be recommended in accordance with the variety of okra used after 15 days of maturity. Seeing its nutritional potential, okra could be very useful to fight against malnutrition.